The loner [large type] - Palmer, Diana (Palmer, Diana. Long, tall Texans series, 2023)
"Tanner Everett spends most of his time jet-setting around the world. But that hasn't stopped innocent Stasia Bolton, the daughter of a neighboring rancher, from falling head-over-heels for the jet-setting playboy. Unbeknownst to Stasia, her father makes it a condition of his will that the ranch will go to her upon his death only if she and Tanner marry, linking the two properties in matrimony. If they don't marry, her ranch will be sold to someone who intends to develop an amusement park on the land. Despite his globetrotting ways, Tanner can't help but be enthralled by the quiet girl next door. As the embers between the two are fanned into flames, Tanner wonders if he's found forever in the last place he ever expected."--